2016
DOI: 10.1016/j.mod.2016.08.003
|View full text |Cite
|
Sign up to set email alerts
|

Regeneration in bipinnaria larvae of the bat star Patiria miniata induces rapid and broad new gene expression

Abstract: Background Some metazoa have the capacity to regenerate lost body parts. This phenomenon in adults has been classically described in echinoderms, especially in sea stars (Asteroidea). Sea star bipinnaria larvae can also rapidly and effectively regenerate a complete larva after surgical bisection. Understanding the capacity to reverse cell fates in the larva is important from both a developmental and biomedical perspective; yet, the mechanisms underlying regeneration in echinoderms are poorly understood. Resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 51 publications
2
17
0
Order By: Relevance
“…Both resulting larval fragments were completely regenerative, restoring all lost tissues and organs over the course of 2 weeks. These findings are consistent with previous reports of larval sea star regeneration [42, 43]. Although we focus on the regeneration of the posterior fragments, a similar regenerative response is apparent within the anterior fragment (Additional file 1: Figure S1).…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…Both resulting larval fragments were completely regenerative, restoring all lost tissues and organs over the course of 2 weeks. These findings are consistent with previous reports of larval sea star regeneration [42, 43]. Although we focus on the regeneration of the posterior fragments, a similar regenerative response is apparent within the anterior fragment (Additional file 1: Figure S1).…”
Section: Resultssupporting
confidence: 91%
“…Larval regeneration is more similar to the WBR observed in planaria and hydra, as it requires the complete re-growth of all tissues and organ systems. Molecular studies of regenerating sea star larvae have identified several regeneration-specific changes in gene expression, including the sea star regeneration-associated protease (SRAP; [41]), vasa , nodal , dysferlin , and vitellogenins ( vtg1 and vtg2 ) [42]. However, to date, a comprehensive survey of gene expression changes during larval echinoderm regeneration has not been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Both resulting larval fragments were completely regenerative, restoring all lost tissues and organs over the course of two weeks. These findings are consistent with previous reports of larval asteroid regeneration [42,43] . Although we focus on the regeneration of the posterior fragments, a similar regenerative response is apparent within the anterior fragment (Figure 2-S2).…”
Section: Bipinnaria Regeneration Involves Wound Healing Body Re-propsupporting
confidence: 94%
“…Larval regeneration is more similar to the WBR observed in planaria and hydra, as it requires the complete re-growth of all tissues and organ systems. Molecular studies of regenerating sea star larvae have identified several regeneration-specific changes in gene expression, including the sea star regeneration-associated protease (SRAP; [41] ), vasa , nodal , dysferlin , and vitellogenins ( vtg1 and vtg2 ) [42] . However, to date, a comprehensive survey of gene expression changes during larval echinoderm regeneration has not been reported.…”
mentioning
confidence: 99%
“…Echinoderm embryos and larvae exhibit a tremendous capacity for regeneration. Research has demonstrated that bisected echinoderm larvae of sea stars (Pisaster ochraceus, Luidia foliolata, and Patiria miniata) and sea urchins (Dendraster excentricus and Lytechinus variegatus) are capable of regrowing the excised portions of their body (Vickery and McClintock, 1998;Vickery et al, 2002;Oulhen et al, 2016). In most cases, the regenerated larvae successfully Luidiidae, order Paxillosida, Ophidiasteridae, order Valvatida, and Oreasteridae, order Valvatida), but genus and species-level identities could not be resolved.…”
Section: Open Questions For Future Researchmentioning
confidence: 99%